ESAFIOS IN INCLUSIVE PEDAGOGICAL PRACTICES IN THE PROCESS OF LITERACY AND LITERACY - Medeiros, Elizabete Maria Goncalves Tabosa; Lima, Luciana Maria Tabosa de; Oliveira, Margarete Maria Goncalves Tabosa de; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Although we are facing a challenging scenario, the pedagogical practices and activities worked with the student with special needs, when it comes to literacy and literacy, goes through different obstacles, ranging from the reception to the training of educators and collaborators who need to adapt to the new needs of the students. It is up to the school to adapt to the demands of students who arrive with their limitations, whether physical or intellectual, putting the educator in new challenges of including this individual within the school learning activities. Given this context, the following question arises: What resources or tools can the educator have to face the challenges of inclusion in the process of literacy and literacy? Therefore, inclusive education comes to address how the regular school has applied and evaluated its pedagogical practices thought in the perspective of inclusion, better understanding its norms, methodologies, actions, guidelines and curricular guidelines that can be developed during the school year. This article is a bibliographic research, of descriptive character of qualitative approach. The sources used were scielo and scirus. It was used as a source: books, articles, dissertations and theses of scientific websites. Among the results portrayed in this article we have: process of curricular adaptation through the Pedagogical Political Project, didactic-pedagogical strategies, teacher training, as well as alternative spaces such as libraries, to motivate students to learn. Thus, it was found that building new pedagogical practices can help in the inclusion of students with special needs, respecting their desires, needs and potentialities.